Relationships between nitric oxide-mediated endothelial function, eNOS coupling and blood pressure revealed by eNOS-GTP cyclohydrolase 1 double transgenic mice. - Adlam, D; Bendall, J; De Bono, J; Alp, N; Khoo, J; Nicoli, T; Yokoyama, M; Kawashima, S; Channon, K (2007)
Endothelium-dependent relaxation in conduit vessels is mediated largely by nitric oxide (NO), produced by the enzyme endothelial nitric oxide synthase (eNOS) in the presence of the cofactor tetrahydrobiopterin (BH4) and mediated through a cGMP-dependent downstream signalling cascade. Endothelial NOS regulates blood pressure in vivo, and impaired endothelial NO bioactivity in vascular disease states may contribute to systemic hypertension. In the absence of sufficient levels of the cofactor BH4, NO becomes uncoupled from arginine oxidation and eNOS produces superoxide rather than NO. The enzymatic uncoupling of eNOS is an important feature of vascular disease states associated with increased oxidative stress. However, whether eNOS coupling, rather than overall eNOS activity, has specific effects on endothelium-dependent vasorelaxation in vitro, or on blood pressure regulation in vivo, remains unclear. In this study, we evaluate the relationships between blood pressure and endothelial function in models of eNOS uncoupling, using mice with endothelium-targeted transgenic eNOS overexpression (eNOS-Tg), in comparison with littermates in which eNOS coupling was rescued by additional endothelium-targeted overexpression of GTP cyclohydrolase 1 (eNOS/GCH-Tg) to increase endothelial BH4 levels. Despite the previously characterized differences in eNOS-dependent superoxide production between these animals, we find that blood pressure is equally reduced in both genotypes, compared with wild-type animals. Furthermore, both eNOS-Tg and eNOS/GCH-Tg mice exhibit similarly impaired endothelium-dependent vasorelaxation. We show that reduced vasorelaxation responses result from desensitization of cGMP-mediated signalling and are associated with increased NO production rather than changes in superoxide production.